Pengaruh Metode Resitasi dalam Pembelajaran Tari Sedulang Setudung pada kegiatan Ekstrakurikuler di Sekolah Menengah Kejuruan Nahdlatul Ulama’ Muara Padang Kabupaten Banyuasin - Amin Novita Sari; Efita Elvandari; Rio Eka Putra (Mahesa Research Center, 2022)
The purpose of this study was to determine whether the recitation method had an influence in learning the sedulabf setudung dance on extracurricular activities at SMK NU Muara Padang, Banyuasin Regency. The theory used by the researcher is the theory of Roestiyah about teaching and learning strategies. The type of reseach used is pre-experimental design One-Group pretest-posttest. The subjects in this study were all students who took part in dance extracurriculars at SMK NUMuara Padang, Banyuasin Regency. The sample used is 27 students. Data collection teachniques used by researchers are observation, performance testd, documentation. The data analysis teachnique used by the researcher is normality test and hypothesis testing. The results of this study indicate the influence of the recitation method in learning the sedulang setudung dance which can be seen from thirung≥trabel and = no effect, = no effect, with the results tcount 7.53 table=2.00.